TRANSFORMASI CERITA KOLONIAL DALAM TEKS “ORANG RANTAI” - Yosi Wulandari; Wachid Eko Yosi; Fitri Merawati (Balai Bahasa Kalimantan Barat, 2019)
The purpose of this study is to describe (1) the authors' reception of the colonial discourse in the text of